2016
DOI: 10.1038/srep36602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage practices and straw incorporation on soil aggregates, organic carbon, and crop yields in a rice-wheat rotation system

Abstract: In this study, a fixed-site field experiment was conducted to study the influence of different combinations of tillage and straw incorporation management on carbon storage in different-sized soil aggregates and on crop yield after three years of rice-wheat rotation. Compared to conventional tillage, the percentages of >2 mm macroaggregates and water-stable macroaggregates in rice-wheat double-conservation tillage (zero-tillage and straw incorporation) were increased 17.22% and 36.38% in the 0–15 cm soil layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 38 publications
8
56
0
Order By: Relevance
“…This may be due to the excessive amount of incorporated crop straw, which could not be mineralized or appropriately decomposed. Previous studies [52,53] also stated that higher amounts of straw incorporation affected the emergence rate of the rice crop and the growth quality at the seedling stage. These findings are also supported by prior research [23,28,54], which concluded that higher rice grain yields were produced by the balanced input of residue with RT methods compared to the control or other nutrient management practices.…”
Section: Discussionmentioning
confidence: 88%
“…This may be due to the excessive amount of incorporated crop straw, which could not be mineralized or appropriately decomposed. Previous studies [52,53] also stated that higher amounts of straw incorporation affected the emergence rate of the rice crop and the growth quality at the seedling stage. These findings are also supported by prior research [23,28,54], which concluded that higher rice grain yields were produced by the balanced input of residue with RT methods compared to the control or other nutrient management practices.…”
Section: Discussionmentioning
confidence: 88%
“…A higher amount of silt-and clay-sized fractions was observed in the control (43.84%). Song et al, (2016) observed that zero tillage and straw incorporation also increased the mean weight diameter and stability of the soil aggregates.…”
Section: Water Stable Aggregates (Wsa)mentioning
confidence: 85%
“…Among the macro-aggregates, 0.25-0.50 mm fraction constituted the largest proportion and had higher C density compared to micro-aggregates. Song et al, (2016) reported that compared to conventional tillage, the percentages of >2mm macro aggregates and water-stable macroaggregates in rice-wheat double-conservation tillage (zero-tillage and straw incorporation) were increased 17.22% and 36.38% in the 0-15 cm soil layer and 28.93% and 66.34% in the 15-30 cm soil layer, respectively. In surface soil (0-15cm), the maximum proportion of total aggregated carbon was retained with 0.25-0.106mm aggregates, and rice-wheat double-conservation tillage had the greatest ability to hold the organic carbon (33.64g kg −1 ) it is evident that the MBC contents in both surface and sub-surface soil were significantly higher in plots receiving 50% RDN as CF+50% RDN as FYM ( F 5 ) Aggregate-associated organic carbon Das et al, (2014) revealed that the long term application of organics increased aggregate associated C as compared in all aggregate size fractions; the highest increase was observed in plots receiving NPK and FYM in combination.…”
Section: Aggregation and Structural Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in soil pH may be associated with organic acids produced by decomposition of the straw [10]. Application of organic matter such as straw can increase the adsorption capacity of heavy metals in the soil, reduce the bioavailability of heavy metals, and reduce the available soil Cd concentration [9,10]. The organic acids and water-soluble organic carbon released from decomposition of straw can activate Cd in the soil Rice and rape -and increase the available Cd concentration in the soil [13,33].…”
Section: Discussionmentioning
confidence: 99%